ANALYSIS OF VILLAGE GOVERNMENT IN EMPOWERING WOMEN'S FARMER GROUPS IN FAMILY FOOD SECURITY(Study in Sukadadi Village, Gedong Tataan Subdistrict, Pesawaran Regency) - Kris Ari Suryandari; Andri Marta; Devilia Astuti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
In the Indonesian government structure, the village is the lowest form of administrative area. In Law No. 6 of 2014, Article 26 paragraph 1 explains that the village head is tasked with organizing village government, implementing village development, village community development, and village community empowerment. One of the empowerment of Sukadadi Village, Gedong Tataan District, Pesawaran Regency is the Women Farmers Group. The Sukadadi Village Women Farmers Group was formed to provide a forum for women to participate in advancing agriculture in the village, especially in food security. The Women Farmers Group can also be a non-formal learning medium to develop the knowledge and skills of its members. The method used in this study is a descriptive method with a qualitative approach. This type of research uses field research. Regarding data collection, there are three stages used in this study: Observation, Interviews, and Documentation. The results of this study indicate that the role of the Sukadadi Village Apparatus, Gedong Tataan District, Pesawaran Regency has been running well, this can be seen from the formation of Women Farmers Groups (KWT) in each hamlet. So that the village is able to prepare resources, utilize opportunities, increase capacity (knowledge and skills), and community participation to achieve family food security, namely by having food availability, food access, and utilization of food obtained from the harvest carried out by the Women Farmers Group (KWT) of Sukadadi Village, Gedong Tataan District, Pesawaran Regency.